Bidirectional Relationships between Alcohol-Specific Parental Socialization Behaviors and Adolescent Alcohol Misuse. (24th August 2018) - Cox, Melissa J.; Ennett, Susan T.; Foshee, Vangie; Hussong, Andrea; Lippold, Melissa; McNaughton-Reyes, H. Luz
ABSTRACT: Background : Although numerous studies have examined parental influence on adolescent alcohol misuse, few have examined how adolescents impact parental behavior or the reciprocal nature of parent-adolescent behavior relative to alcohol misuse. Objectives : This study assessed bidirectional relationships between adolescent alcohol misuse and three alcohol-specific parenting behaviors (substance-specific monitoring, permissive communication messages about alcohol, and cautionary communication messages about alcohol). Methods : Data were from 1, 645 parent-adolescent dyads drawn from a longitudinal study spanning grades 6–10. A multivariate latent curve model with structured residuals was used to test study hypotheses. Results : One marginally significant result emerged (increased alcohol misuse leads to greater substance-specific monitoring) after accounting for underlying developmental processes. Conclusions : Though practical implications are limited based on the results of the study, further directions for research regarding study design and measurement are provided to more fully examine dynamic processes between parents and adolescents relative to alcohol use.